Dekonstruksi Peran Pustakawan - Wiji Suwarno (Pustabiblia: Journal of Library and Information Science, 2019)
The theme of this article is the role of librarians in disruption era. This study uses qualitative research with a phenomenological approach. The informants from this study were librarians from all elements who visited and were met at IAIN Saaltiga. Informant was taken randomly. Data collection is done using interviews and documents. The problem of this research is the strategy to development that threatens to shift the role of librarians. The results of this study are that librarians are required to map their developments, weaknesses, and develop the skills needed according to development. The reliability of the librarian is an advanced point of professionalism which is then oriented to the ability to maintain self quality. Competency is the ability in terms of Listening, Informatin acceptance, Public relations, Social relationships, Time management, Interpersonal, and Communication skills.